2020
DOI: 10.1016/j.ajic.2020.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of SARS-CoV-2 to UV irradiation

Abstract: Highlights SARS-CoV-2 is highly susceptible to irradiation with ultraviolet light. High viral loads of 5 * 10 6 TCID 50 /ml SARS-CoV-2 can be inactivated in 9 minutes by UVC irradiation. UVC irradiation represents a suitable disinfection method for SARS-CoV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
312
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(337 citation statements)
references
References 5 publications
14
312
0
11
Order By: Relevance
“…A recent study looked at the combined effectiveness of UV-A/UV-C irradiation of SARS-CoV-2 in comparison to UV-A or UV-C alone 10 . The study found that UV-A was a poor means of inactivating SARS-CoV-2 in comparison to inactivation by 1.94 mW/cm 2 UV-C. Of note, our results were generated using a lower dose of UV-C (0.849 mW/cm 2 ) and a quicker time (4 – 9 s rather than 9 min with UV-C alone).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study looked at the combined effectiveness of UV-A/UV-C irradiation of SARS-CoV-2 in comparison to UV-A or UV-C alone 10 . The study found that UV-A was a poor means of inactivating SARS-CoV-2 in comparison to inactivation by 1.94 mW/cm 2 UV-C. Of note, our results were generated using a lower dose of UV-C (0.849 mW/cm 2 ) and a quicker time (4 – 9 s rather than 9 min with UV-C alone).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of different commercially available mouthwashes based on the well-established antiseptically effective actives chlorhexidinedigluconate (CHX) and octenidinedihydrochloride (OCT) was conducted considering the European Standard EN 14476 [7]. The assays were carried out using an isolated SARS-CoV-2 outbreak strain [8] in the presence of low organic soiling (i.e. 0.3 g/L bovine serum albumin) as requested by EN 14476 [7] to also consider potential quenching of the actives by protein load as has been described before [9].…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative suspensions tests were carried out as described in EN 14476 [7]. Briefly, efficacy against SARS CoV-2 [8] was studied using commercially available mouthwashes. A commercially available ready-to-use formulation designated formulation A (100 g contains: 0.1 g Chlorhexidine bis-(D-gluconate); GlaxoSmithKline Consumer Health GmbH & Co. KG, Germany) was used as one test formulation.…”
Section: Methodsmentioning
confidence: 99%
“…While germicidal UVC is likely more effective, there is evidence that other wavelengths of light have germicidal properties, including, far-UVC (222 nm), UVB, UVA, visible (400–700 nm) and infrared ( 92 ). It is likely that higher doses of these wavelengths will be required for a similar efficacy as germicidal UVC (254 nm), which was more effective than UVA (365 nm) at inactivating SARS-CoV-2 ( 93 ).…”
Section: Could Uv Light Have Harmful or Beneficial Effects On Covid-1mentioning
confidence: 99%